Determinants of auditors' usage of digital analysis audit software / Nortasha Ismail - Ismail, Nortasha (2014)
Recently, a business database is emerging and developing with numerous and integrated applications. Such advancement has made abnormalities more difficult to discover, and it presents important challenges for auditors to investigate without applying a sophisticated audit analysis tools (Salem, 2012). Therefore, the introduction of digital analysis in audit software is believed could provide auditors with a necessary tool to perform audits in large quantities of data (Nigrini, 1999). Nonetheless, the perception and usage of digital analysis audit software among auditors in Malaysia is still low (Mahzon & Veerankuthy (2010). This study is conducted to determine the factors that affect the usage of digital analysis audit software among auditors using a set of the questionnaire survey.